SOCIAL-PSYCHOLOGICAL MECHANISMS OF HUSBAND-WIFE RELATIONS IN THE MODERN FAMILY - Panoyeva Dilshoda Erkin qizi (Journals Park Publishing, 2023)
This article presents information about the researches of Eastern and Western scientists on family relations, family types, socio-psychological characteristics of the relations of husband and wife in the family.
Keywords: family type, patriarchal, detocentric, psychoanalytic concept, specific function, reproductive function, protective function.